Good cochlear implantation outcomes in subjects with mono-allelic WFS1-associated sensorineural hearing loss – a case series. - Fehrmann, M. L. A.; Lanting, C. P.; Haer-Wigman, L.; Mylanus, E. A. M.; Huinck, W. J.; Pennings, R. J. E. (International Journal of Audiology, 2025)
Objective: This study aimed to evaluate long-term cochlear implant (CI) outcomes in individuals with mono-allelic pathogenic variants in WFS1, which is associated with both Wolfram-like syndrome and DFNA6/14/38. Design: Retrospective case series. Study sample: Seven CI recipients, ranging from eight months to 58 years of age, were included in the study, including four with Wolfram-like syndrome and three with DFNA6/14/38. A total of ten cochlear implantations were performed among these subjects. Results: At one-year post-implantation, a mean phoneme score of 90 ± 9% at 65 dB SPL in quiet was found, which remained stable up to ten years post-implantation with a mean phoneme score of 94 ± 6%. Despite these excellent outcomes, one subject achieved no speech recognition with CI and eventually became a non-user. This individual had a prolonged absence of auditory stimulation prior to implantation and encountered multiple challenges during rehabilitation. Conclusion: Individuals with Wolfram-like syndrome or DFNA6/14/38 demonstrate consistently good outcomes following implantation, which remain stable over time. These findings affirm cochlear implantation as an effective rehabilitation option for these individuals. Furthermore, the stable and good CI outcomes contradict the suggested link between WFS1-associated sensorineural hearing loss and auditory neuropathy.